Shedding light on the composition of extreme microbial dark matter: alternative approaches for culturing extremophiles - Schultz, Júnia; Modolon, Flúvio; Peixoto, Raquel Silva; Rosado, Alexandre Soares (Frontiers in Microbiology, 2023)
More than 20,000 species of prokaryotes (less than 1% of the estimated number of Earth’s microbial species) have been described thus far. However, the vast majority of microbes that inhabit extreme environments remain uncultured and this group is termed “microbial dark matter.” Little is known regarding the ecological functions and biotechnological potential of these underexplored extremophiles, thus representing a vast untapped and uncharacterized biological resource. Advances in microbial cultivation approaches are key for a detailed and comprehensive characterization of the roles of these microbes in shaping the environment and, ultimately, for their biotechnological exploitation, such as for extremophile-derived bioproducts (extremozymes, secondary metabolites, CRISPR Cas systems, and pigments, among others), astrobiology, and space exploration. Additional efforts to enhance culturable diversity are required due to the challenges imposed by extreme culturing and plating conditions. In this review, we summarize methods and technologies used to recover the microbial diversity of extreme environments, while discussing the advantages and disadvantages associated with each of these approaches. Additionally, this review describes alternative culturing strategies to retrieve novel taxa with their unknown genes, metabolisms, and ecological roles, with the ultimate goal of increasing the yields of more efficient bio-based products. This review thus summarizes the strategies used to unveil the hidden diversity of the microbiome of extreme environments and discusses the directions for future studies of microbial dark matter and its potential applications in biotechnology and astrobiology.